The Effect of Fartlek Training on the Increase of Cardiorespiratory Endurance in Kumite Karateka of the Gokasi Student Activity Unit Unsoed - Fais oktavian syah; Ayu Rizky Febriani; Dewi Aggraeni; Mohammad Nanang Himawan Kusuma; Jajang Dede Mulyani (Department of Physical Education, Faculty of Health Sciences, Universitas Jenderal Soedirman, 2025)
Cardiovascular endurance is a crucial component for karate athletes, especially in kumite, where matches require high aerobic and anaerobic capacity. However, the lack of consistent physical training programs often leads to suboptimal performance in student athletes. This study aimed to determine the effect of Fartlek training on improving cardiorespiratory endurance in karate athletes of the Gokasi Student Activity Unit, Universitas Jenderal Soedirman. This research employed a quasi-experimental design with a nonequivalent control group. The population consisted of 32 athletes, from which 20 samples (12 males and 8 females) were selected using purposive sampling. The treatment group underwent Fartlek training for 16 sessions over 4–5 weeks, while the control group continued routine practice without intervention. Cardiorespiratory endurance was measured using the Multistage Fitness Test (MFT) to obtain VO₂max values. Data analysis used paired sample t-test and independent sample t-test with a significance level of 0.05. Result: The paired sample t-test showed a significant increase in VO₂max in the treatment group (p = 0.000), while no significant change was observed in the control group (p = 0.651). The independent t-test revealed a significant difference between the treatment and control groups in post-test results (p = 0.047). Conclusion: Fartlek training has a significant effect on improving cardiorespiratory endurance (VO₂max) in karate athletes. Therefore, it can be considered an effective training method to enhance performance in kumite athletes.